Estimating the Generalized Exponential Distribution Parameters and the Acceleration Factor under Constant-Stress Partially Accelerated Life Testing with Type-II Censoring - Ismail, A.A. (Проблемы прочности, 2013)
Accelerated life testing (ALT) and partially accelerated
life testing (PALT) are frequently used
in modern reliability engineering. ALT and
PALT are run to obtain information on the life
of the products and materials in a shorter time
and at lower cost. The experimental units are
subject to stress conditions that are more severe
than those encountered in normal use condition
to induce early failures. ALT or PALT can be
carried out using constant, step, progressive, cyclic
and random stress loadings. This paper considers
the problem of estimating the generalized
exponential (GE) distribution parameters and
the acceleration factor under constant-stress
PALT model. The main objective is to derive the
maximum likelihood estimators (MLEs) of the
parameters of the GE distribution and the acceleration
factor when the data are type-II censored
from constant-stress PALT. Also, the performance
of the MLEs is investigated numerically
for different sample sizes and different parameter
values using the mean square error. In addition,
the approximate confidence intervals of the
model parameters are constructed. Moreover,
the likelihood ratio bounds (LRB) method is
used to obtain confidence bounds of the model
parameters when the sample size is small. For
illustration, a simulation study is conducted. It
is observed that the simulation results support
the theoretical findings. Ускоренные и частично ускоренные ресурсные испытания часто проводятся для обеспечения
надежности современной техники. Цель таких испытаний – за короткий срок и с меньшими
затратами получить информацию о ресурсе изделий и материалов. Испытания можно
проводить при постоянных, ступенчатых, прогрессирующих и циклических нагрузках, а
также при нагрузке случайным напряжением. Рассматривается задача оценки параметров
обобщенного экспоненциального распределения и коэффициента ускорения в условиях частично ускоренного ресурсного испытания с постоянным напряжением. С использованием среднеквадратической погрешности проведено численное исследование эффективности оценки методом максимального правдоподобия для разных размеров образцов и значений параметра.
Для параметров модели построены приблизительные доверительные границы. Чтобы получить доверительные границы для параметров модели в случае образца маленького размера,
использовали метод отношения правдоподобия. В качестве примера проведено исследование с
помощью моделирования. Показано, что результаты моделирования согласуются с данными
расчетов. Прискорені та частково прискорені ресурсні випробування часто проводяться
для забезпечення надійності сучасної техніки. Метою таких випробувань є за
короткий проміжок часу та з найменшими затратами отримати інформацію
про ресурс виробів і матеріалів. Випробування можна проводити за постійних, східчастих, прогресуючих і циклічних навантажень, а також при навантаженні випадковим напруженням. Розглядається задача оцінки параметрів
загального експоненціального розподілу та коефіцієнта прискорення в умовах частково прискореного ресурсного випробування з постійною напругою.
Із використанням середньоквадратичної похибки проведено чисельне дослідження ефективності оцінки методом максимальної правдоподібності для різних розмірів зразка та значень параметра. Для параметрів моделі побудовано
приблизні довірчі границі. Щоб отримати довірчі границі для параметра
моделі у випадку зразка маленького розміру, використовували метод відношення правдоподібності. Як приклад проведено дослідження за допомогою
моделювання. Показано, що результати моделювання збігаються з даними
розрахунків.